SOCIALIZING THE IMPORTANCE OF ANTI-CORRUPTION EDUCATION FOR SCHOOL STUDENTS - Resi, Erfanus; Mari, Mikhael; Kaha, Hendrikus Likusina; Lawalu, Stepanie Perdana Ayu; Molan, Kristianus Simon H (LPPM Universitas Flores, 2025)
The root of corruption lies in fostering an understanding of anti-corruption behaviour among students, which requires an understanding and application of anti-corruption values and principles from an early age. This issue is closely related to social control in educational and community environments, which forms the basis for prevention strategies. The younger generation is the nation's most valuable asset that will shape the future of Indonesia. This community service aims to instil the values of honesty, integrity, and social responsibility in students of SMP Negeri 3-SATAP Amarasi Selatan, as the nation's next generation, so that they develop a strong awareness of the dangers of corruption and cultivate anti-corruption attitudes from an early age. In addition, this activity aims to increase students' understanding of various forms of corruption in the school and community environment, as well as to shape characters who actively prevent and fight corrupt practices. The methods applied in this community service activity involve observation and learning through social interaction. The results of the study indicate that anti-corruption education with interactive educational methods such as presentations, group discussions, case simulations, and quizzes effectively increases students' understanding and commitment to the values of honesty, integrity, and social responsibility. It can be concluded that anti-corruption education is very important to be instilled in junior high school students from an early age. A follow-up to this activity is the importance of continuously integrating anti-corruption education into the school curriculum and extracurricular activities. Furthermore, teacher training is needed to reinforce integrity materials in teaching. Parental and community involvement is also crucial in supporting the development of children's character, free from the influence of corruption.